Evaluation of natural extracts against Bemisia tabaci in melon crops, Puntarenas, Costa Rica - Corrales Castillo, Jordan (2018)
The aim of this study was to analyze the effect of three natural repellents made from extracts of thyme, chile/garlic and cinnamon/clove for decreasing whitefly infestation on melon crops in Costa Rica and be included in combat proposals and thus reduce control costs. The effectiveness of these organic products were examined in relation to a control treatment using a common insecticide (Plural 20 OD Imidacloprid). The study was carried out on a farm owned by the agricultural company MAYAN of Orotina S.A in Esparza, Puntarenas, Costa Rica. We used a completely randomized experimental design of repeated measurements for 3 treatments with 3 replicates, where the effect of repellence was determined by counting white flies before and after applications and fitting these counts to an Average Infestation Index (IMI). Then, the percentage of efficiency of the extracts was established depending on whether IMI increases or decreases. The statistical analysis was performed using IMI whit a Wilcoxon signed rank test implement in order to contrast the IMI to determine the distributions just before and after the applications were applied. Finally a Generalized Linear Model (MLG) was implemented to detail data pattern and variability. The treatment that showed best efficiency in controlling the white fly pest was the commercial insecticide, but the efficiency decreased over the time. The treatment that best repel white fly population was obtained using the extract of cinnamon/clove, this effect persisted for a longer time. No statistically significant differences were found between natural extract repellents; the only differences were in treatments versus control. It was concluded that for a rapid decrease the insecticide can be used, but for a decrease over time the natural insecticides in conjunction with the chemical are the best option within an integrated management plan.